Drier tropical forests are susceptible to functional changes in response to a long‐term drought. (4th March 2019) - Aguirre‐Gutiérrez, Jesús; Oliveras, Imma; Rifai, Sami; Fauset, Sophie; Adu‐Bredu, Stephen; Affum‐Baffoe, Kofi; Baker, Timothy R.; Feldpausch, Ted R.; Gvozdevaite, Agne; Hubau, Wannes; Kraft, Nathan J. B.; Lewis, Simon L.; et al.
Abstract: Climatic changes have profound effects on the distribution of biodiversity, but untangling the links between climatic change and ecosystem functioning is challenging, particularly in high diversity systems such as tropical forests. Tropical forests may also show different responses to a changing climate, with baseline climatic conditions potentially inducing differences in the strength and timing of responses to droughts. Trait‐based approaches provide an opportunity to link functional composition, ecosystem function and environmental changes. We demonstrate the power of such approaches by presenting a novel analysis of long‐term responses of different tropical forest to climatic changes along a rainfall gradient. We explore how key ecosystem's biogeochemical properties have shifted over time as a consequence of multi‐decadal drying. Notably, we find that drier tropical forests have increased their deciduous species abundance and generally changed more functionally than forests growing in wetter conditions, suggesting an enhanced ability to adapt ecologically to a drying environment.